2017
DOI: 10.3389/fmicb.2017.01614
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Antibiotic Chemotherapies on Pseudomonas aeruginosa Infection In Vitro of Primary Human Corneal Fibroblast Cells

Abstract: Pseudomonas aeruginosa is a major cause of bacterial keratitis (BK) worldwide. Inappropriate or non-optimal antibiotic chemotherapy can lead to corneal perforation and rapid sight loss. In this study, we tested the hypothesis that P. aeruginosa strain PAO1 invades primary human corneal fibroblasts (hCFs) in vitro and persists intracellularly, despite chemotherapy with antibiotics used commonly to treat BK. In rank order, ciprofloxacin, levofloxacin and polymyxin B showed the highest activity against planktonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 60 publications
(84 reference statements)
1
9
0
Order By: Relevance
“…Furthermore, the CFTR protein has been postulated to be important for P. aeruginosa internalization inside lung epithelial cells [ 25 ], which supports the idea that the clinical CF isolates PAET1, PAET2, and PAET4 may have undergone directed adaptation to allow them to colonize CFBE41o- cells, as we have detected in our work. Inside the cell, P. aeruginosa can persist and replicate intracellularly, as detected in our study as well as in other cellular models [ 7 , 17 , 25 ]. Bacterial persistence within host cells can constitute a latent reservoir that is helped by the poor intracellular penetration of some antibiotics and can lead to the selection of antibacterial resistant mutants and contribute to disease harshness and chronicity [ 7 , 21 ].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Furthermore, the CFTR protein has been postulated to be important for P. aeruginosa internalization inside lung epithelial cells [ 25 ], which supports the idea that the clinical CF isolates PAET1, PAET2, and PAET4 may have undergone directed adaptation to allow them to colonize CFBE41o- cells, as we have detected in our work. Inside the cell, P. aeruginosa can persist and replicate intracellularly, as detected in our study as well as in other cellular models [ 7 , 17 , 25 ]. Bacterial persistence within host cells can constitute a latent reservoir that is helped by the poor intracellular penetration of some antibiotics and can lead to the selection of antibacterial resistant mutants and contribute to disease harshness and chronicity [ 7 , 21 ].…”
Section: Discussionsupporting
confidence: 83%
“…However, the invasion rates and the levels of intracellular persistence and replication were found to be cell- and strain-dependent. The invasion capacity of the P. aeruginosa strains within host cells in vitro notwithstanding the P. aeruginosa phenotype have been broadly observed [ 7 , 17 , 21 , 23 ]. It should be noted that there is heterogeneous genotypic clonality among P. aeruginosa infections as well as different protein expression profiles (including important virulence factors) that depend on the P. aeruginosa background [ 4 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also found that bactericidal and bacteriostatic antibiotics used in bacterial keratitis were unable to eradicate Pseudomonas infection of human fibroblasts culture in vitro. Their effectiveness depends on the cellular location of Pseudomonas [36].…”
Section: Management Of P Aeruginosa Keratitismentioning
confidence: 99%